Induced first abortion rates before and after HIV diagnosis: results of an Italian self‐administered questionnaire survey carried out in 585 women living with HIV. Issue 1 (26th June 2012) - Ammassari, A; Cicconi, P; Ladisa, N; Di, F; Bini, T; Trotta, MP; D'Ettorre, G; Cattelan, AM; Vichi, F; d'Arminio Monforte, A; ,
<x xml:space="preserve">Abstract</x> Objectives The aim of the study was to investigate whether HIV diagnosis affected reproductive planning over time and to assess independent predictors of abortion overall and following HIV diagnosis. Methods Donne con Infezione da HIV (DIDI) is an Italian multicentre study based on a questionnaire survey carried out in 585 HIV‐positive women between November 2010 and February 2011. The incidence and predictors of abortion were measured by person‐years analysis and Poisson regression. Results The crude incidence rate of abortion was 18.8 [95% confidence interval (CI) 16.5–21.4] per 1000 person‐years of follow‐up (PYFU). Compared with women who terminated their pregnancy before HIV diagnosis, women who terminated their pregnancy after HIV diagnosis but before 1990 showed a 2.56‐fold (95% CI 1.41–4.65) higher risk. During 1990–1999 and 2000–2010, HIV diagnosis was not significantly associated with outcome [adjusted rate ratio (ARR) 0.93 (95% CI 0.55–1.59) and ARR 0.69 (95% CI 0.32–1.48), respectively]. Age [ARR 0.96 (95% CI 0.94–0.99) per 1 year older] and injecting drug use [ARR 1.38 (95% CI 0.98–1.94)] were found to be predictors of abortion overall. After HIV diagnosis, being on combination antiretroviral therapy [ARR 0.54 (95% CI 0.28–1.02)], monthly income < €800 [ARR 1.76 (95% CI 0.99–3.12)], younger age [ARR 0.95 (95% CI 0.91–1.00) per 1 year older] and fear of vertical transmission [ARR 1.95 (95% CI 1.04–3.67)] were found to be independently associated with abortion. Conclusions We observed a higher incidence of abortion compared with data available for the general Italian population. Awareness of HIV diagnosis was predictive of abortion only in the 1980s. Women with HIV infection are still worried about vertical HIV transmission. Interventions promoting HIV screening among women who plan to have an abortion and informative counselling on motherhood planning in the setting of HIV care are needed.